Formation of the professional qualities of a doctor in first-year students on the base of modern technologies - Popovych, A. P.; Аlieva, O. H.; Попович, Аліса Петрівна; Алієва, Олена Геннадіївна (Полтава : ДЗ "ЛНУ імені Тараса Шевченка", 2023)
Abstract. Education is one of the priority areas of society’s development. It is ensured by the quality of education, which depends on many factors. The most effective ICT methods and their role in shaping the professional qualities of the future doctor in the process of training 1st-year students have been determined.
Keywords: ICT; teaching methods; communicative competence